Understanding Colourism Through Social Media Discourse (Twitter) Among Malaysians - Zulkifli, Zulfati Izazi (2021)
This research is designed to study the pervasiveness of colourism in Malaysia through discourses on the subject of skin colour that subsist on social media. Colourism is essentially defined as a prejudice or discrimination based on skin colour. Principally, this thesis discovers the commonly subtle act of colourism in the society by concentrating on the discursive strategies and linguistic devices implemented in their digital discourse. To accomplish this, a theoretical framework composed of Computer- Mediated Discourse and Discourse-Historical Approach is formulated. To strengthen the interpretation of discourse, the analysis is supported by Sociocognitive Approach and Representation Theory. A method of organising the presentation of data is adapted from the construction of Thematic Analysis. The composition of data is achieved by conducting a virtual fieldwork, followed by a convenience sampling method of data collection performed on a social media site called Twitter. This is a qualitative research that reveals the underlying ideology through the construction of language in the discourse of skin colour. The findings from this study suggests that colourism is evidently present in Malaysia. A number of themes arise from their discourse about skin colour, predominantly on the subject of beauty, self-esteem, skin bleaching, and gender bias. Their discourse is realised through discursive strategies such as nomination, predication, and argumentation, along with constructive linguistic devices such as deixis, rhetoric, and verbs of feelings